Republic of Madagascar : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The Poverty Reduction Strategy Papers (PRSPs) on the Republic of Madagascar explain the Madagascar Action Plan (MAP) to accelerate and better coordinate the development process. The National Leadership Institute of Madagascar (NLIM) was created in 2006 to provide cutting-edge training to build leadership capacity at all levels of government and for all sectors of society. The Economic Development Board of Madagascar (EDBM) is charged with ensuring that the business climate of Madagascar is attractive for companies and conducive for the success of private enterprises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet